Zebrafish neural tube morphogenesis requires scribble-dependent oriented cell divisions - Žigman, Mihaela (Current biology, 2011)
Summary: How control of subcellular events in single cells determines morphogenesis on the scale of the tissue is largely unresolved. The stereotyped cross-midline mitoses of progenitors in the zebrafish neural keel [1-4] provide a unique experimental paradigm for defining the role and control of single-cell orientation for tissue-level morphogenesis in vivo. We show here that the coordinated orientation of individual progenitor cell division in the neural keel is the cellular determinant required for morphogenesis into a neural tube epithelium with a single straight lumen. We find that Scribble is required for oriented cell division and that its function in this process is independent of canonical apicobasal and planar polarity pathways. We identify a role for Scribble in controlling clustering of α-catenin foci in dividing progenitors. Loss of either Scrib or N-cadherin results in abnormally oriented mitoses, reduced cross-midline cell divisions, and similar neural tube defects. We propose that Scribble-dependent nascent cell-cell adhesion clusters between neuroepithelial progenitors contribute to define orientation of their cell division. Finally, our data demonstrate that while oriented mitoses of individual cells determine neural tube architecture, the tissue can in turn feed back on its constituent cells to define their polarization and cell division orientation to ensure robust tissue morphogenesis.